THE RELATIONSHIP BETWEEN SOCIAL MEDIA ADDICTION AND SOCIAL ANXIETY AMONG UNIVERSITY SELANGOR (UNISEL) STUDENTS - MOHD KHAIZAN, NURULIMAN; JALIL, NUR ANIS SYAFIQAH; KAMSUN BAHARIN, KHAIRISA BALQIS BAHARIN; KASIM, NUR MUNEERAH (Selangor Humaniora Review, 2025)
Abstract Social media is a network of online platforms and technologies that provides a valuable space for individuals to connect and communicate with each other. However, the excessive use of social media can lead to the emergence of social media addiction and subsequently increased negative consequences on users' mental health. Hence, this study wants to investigate the relationship between social media addiction and social anxiety among students at the University of Selangor (UNISEL). This study applied a quantitative approach to explore the issues of social media addiction and social anxiety. For data collection, 101 students from UNISEL responded to the questionnaire by filling in Google Forms. The items of the questionnaire are adapted from the Bergen Social Media Addiction Scale (BSMAS) and the Interaction Anxiety Scale (IAS). Then, to answer the research hypothesis, the data was analyzed through a statistical software, Statistical Packages for Social Sciences (SPSS) by carrying out a Pearson's correlation test. The findings discovered that there is no significant relationship between social media addiction and social anxiety, thus the hypothesis is rejected. The absence of significant findings might be ascribed to various reasons, including the participants' demographic and cultural backgrounds, the limits of the measuring instruments, and the specific nature of social media use among UNISEL students. Therefore, this study may be beneficial for future researchers and stakeholders to better understand the issues of social media addiction and social anxiety, which can mitigate the risks or possible factors of these issues. Keywords: Social Media, Social Media Addiction, Social Anxiety, UNISEL Student.